Gratifikasi dalam Perspektif Etika dan Hukum: Antara Budaya Pemberian dan Korupsi - Novara Jaya, Andi Ervin; Majid, Ilham; Utami, Gusti Ayu; Klau, Ricardo Goncalves (Universitas Pahlawan Tuanku Tambusai, 2024)
Gratification is generally considered a gift to public officials as a form of appreciation and thanks. However, this good intention is often misused due to hidden motives that can damage integrity and, worse, lead to acts of corruption that violate the law. The purpose of this research is to examine gratification from ethical and legal perspectives to distinguish between lawful gifts and those that violate regulations based on applicable rules. Gratification, from both ethical and legal perspectives, can damage integrity, trigger conflicts of interest, and harm public interests. In conclusion, the role of law enforcement is needed in implementing the Anti-Corruption Law, which can differentiate between potential bribery and gifts with no special intent. The public also plays a role in preventing gratification by reporting suspected cases, while the Corruption Eradication Commission (KPK) plays a role in combating gratification practices.